Strategie didattico-valutative degli insegnanti. Uno studio esplorativo nella scuola primaria - Anna Maria Ciraci (LED Edizioni Universitarie, 2012)
Teachers' Didactic-evaluation Strategies. An Explorative Study in Primary Schools The study involved all those teachers who enrolled in two academic years in the degree course «Education Sciences in Distance Education Mode» on an e-learning platform, of the Faculty of Education Sciences, «Roma Tre» University. This course was specifically created for the in-service training of pre-school and primary school teachers of the Lazio region. The study aimed to assess, before the start of the university course itself, both the didacticevaluation strategies actually used in class as well as the opinions and attitudes on certain aspects of the teaching profession. What emerges from the data analysis is a professional model which presents certain weaknesses. These refer, in particular, to the competencies necessary to deal with an individualised didactic strategy that can facilitate the reaching of cognitive aims on the part of all the students, and also to the use of reliable evaluation tools not only for learning assessment, but, above all, as a fundamental resource for learning. The contribution refers to research that is still in progress (Domenici, Biasi, & Ciraci, 2012) and geared to assessing - at the end of the course - what impact the degree course has had in terms of enhancing the teachers' real competencies.